Local governance in India - "Joseph, T.M.(ed.)" (New Delhi, 2007)
Book Summary of Local Governmence In India Ideas, Challenges And Strategies This compendium of twenty-eight papers makes a performance appraisal of the local governance mechanism in India for the first ten years of its mandatory existence. It throws light on the ideas behind these institutions, the challenges they Face and the strategies to contain them. Attempting at understanding local governance, the contributors deliberate on decentralisation and development, people's participation in local governance, dynamics and challenges of local governance and the emerging paradigm of local governance. The book will be useful for policy-makers, researchers and development workers. About the Author T.M. Joseph is currently Reader and Head, Department of Political Science, Newman College, Thodupuzha, Kerala. He had his doctoral studies at the Institute for Social and Economic Change, Bangalore on the 'Nativist Movement in Bangalore City'. He also had been a Visiting Fellow at Faculty of Law, Kyushu University, Japan from 1998 to 2000. He has to his Credit a book titled Politics of Recruitment: Migration and Ethic Conflict in Urban India and several Research papers published in leading journals. He is the Principal Investigator for the UGC sponsored major research project on "Paradigm Shift in Governance: State-Society Synergy in Rural Kerala with special reference to the Jalanidhi Project". He is also a member of Board of Studies and a research guide in Political Science in Mahatma Gandhi University.
Keywords: Local government-India